Impacts of Ethnic Conflict on Formal Education in Ghana: A case study of Chereponi District in North-Eastern Ghana - Kwame, Emmanuel (Journal of Public Policy and Administration, 2023)
Purpose: The study set out to explore the impact of conflict on educational activities. Methodology: The study employed a mixed method design where both qualitative and quantitative data was collected.The target population for this study was limited to the stake holders of education in district because they had adequate knowledge about what constitute educational activities and how these are affected by the conflict. These included Teachers, current students, School Management Committee (SMC) members and Parent Teacher Associations (PTAs). Findings: It was also revealed that the impact of the conflict on educational activities were school closures, absenteeism of both teachers and students, movement of teachers to other districts, disruption of examinations and child rights abuse. During the conflicts GES schools were shut down over a year so no academic activities took place during the period. Pupils remained at home with their parents for safety reasons. Unique Contribution to Theory, Practice and Policy: The study recommends that the Ministry of Youth and Local Government may liaise with the National House of Chiefs and the Northern Regional House of Chiefs to employ the indigenous methods of conflict resolution within the district to resolve the conflict between the Chokosis and the Konkombas. The Government of Ghana may formulate policies that will forbid any warring factions from targeting educational facilities or education employees and students so as to prevent instances where communal clashes disrupt academic activities.